2017
DOI: 10.18203/2349-3291.ijcp20171703
|View full text |Cite
|
Sign up to set email alerts
|

Study of CSF C-reactive protein in meningitis to differentiate bacterial meningitis from aseptic meningitis in children between 1 month and 12 years of age

Abstract: Background: Meningitis is a serious illness of childhood. CSF Gram stain and culture is the gold standard for diagnosis which is a costly and time consuming. So, this study was conducted with the objective to measure the specificity, sensitivity, positive and negative predictive values and diagnostic accuracy of CSF-CRP in the diagnosis of bacterial meningitis.Methods: This prospective study was conducted in Department of Pediatrics, National Institute of Medical Sciences and Research, Jaipur. Children between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The similar observations were made by other studies done elsewhere, where the most common isolates were streptococcus pneumonia. 19,20 Among 17,22 The institute mortality of patients with bacterial meningitis was 13.46% which is comparable with the previous studies. 23,24 CRP in CSF was positive in 86 (82.69%) of the CSF samples with culture positivity which was statistically significant (p<0.01) in detecting cases of bacterial meningitis.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The similar observations were made by other studies done elsewhere, where the most common isolates were streptococcus pneumonia. 19,20 Among 17,22 The institute mortality of patients with bacterial meningitis was 13.46% which is comparable with the previous studies. 23,24 CRP in CSF was positive in 86 (82.69%) of the CSF samples with culture positivity which was statistically significant (p<0.01) in detecting cases of bacterial meningitis.…”
Section: Discussionsupporting
confidence: 87%
“…A similar finding was also reported in various other studies. 5,19,22 The level of CRP in CSF is variable and usually less than that of plasma. It depends on the amount of CRP released into CSF from plasma by ultrafiltration and secretion by inflamed meninges.…”
Section: Discussionmentioning
confidence: 99%
“…Belagavi et al 13 has shown that CSF-CRP has sensitivity and specificity of 83.3% and 100%, respectively, with an accuracy of 98% in adults with meningitis. Natani et al 14 conducted a study in children aged between 1 mo and 12 y with meningitis and had shown that CSF-CRP has sensitivity and specificity of 72.92% and 85.71%, respectively, with an accuracy of 78.89%. The study concluded that CSF-CRP can be used as an initial test for the diagnosis of bacterial meningitis.…”
Section: Discussionmentioning
confidence: 99%